A Study of Groundnuts from the Western Area of Libya - Ahdaya, S.; Godin, P. J. (The Libyan Journal of Agriculture, 2023)
Ten samples of groundnuts were examined for the presnce of toxic metabolites of the fungus Aspergillus flavus. Of these samoles, two contain compounds which on the present evidence are Aflatoxin Bl.At first sio-ht it seems unlikelv that “aflatoxin” should be a problem in Libva. It is recommended, however, that a further study should be carried out, including bioassay, on the 1971 crop. In particular, information should be obtained, on drying and storage procedures.